DYNAMICS OF MORTALITY FROM INFECTIOUS AND PARASITIC DISEASES IN THE ALTAI REGION - Дорофеев, Юрий Юрьевич; Колядо, Елена Владимировна; Колядо, Владимир Борисович; Бескровная, Елена Владимировна (Medicine in Kuzbass, 2017)
Subject of the research (observation). Mortality of population from infectious diseases. Objective of the research. To study the basic tendencies of mortality from infectious diseases in the Altai region within the last 5 years. Research methods. Statistical, analytical. Basic results. The realized analysis has revealed the structural changes in reasons of mortality from infectious diseases accompanied by the decrease in the share of the deceased from tuberculosis and the increase in the share of the deceased from HIV-infection. Field of their application. Organization of medical activity. Conclusions. During the 2012-2016 period, in the Altai region there can be observed a considerable change of the structure of mortality from infectious diseases.